2001
DOI: 10.1034/j.1600-0412.2001.800101.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyrtl’s anastomosis, the only connection between the two umbilical arteries. A study in full term placentas from AGA infants with normal umbilical artery blood flow

Abstract: By using angiography we were able to demonstrate the variable anatomy of the anastomosis of Hyrtl. We found the occurrence and width of the anastomosis was correlated to the symmetry in size between the supply areas of each umbilical artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
2
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 16 publications
1
38
2
4
Order By: Relevance
“…1B). The diameters, D 1 ϭ D2 ϭ 4 mm, and arterial length, 80 mm, where L up ϭ Ldown ϭ 40 mm of the umbilical arteries, as well as the geometry of the Hyrtl anastomosis (D anast ϭ 4 mm, Lanast ϭ 8 mm), were chosen from averaged morphometric data (17)(18)(19)25). The downstream resistance of the arterial vasculature in the placental territories, which are supplied by each umbilical artery, is represented by a cylindrical porous media of length L porous ϭ 20 mm (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1B). The diameters, D 1 ϭ D2 ϭ 4 mm, and arterial length, 80 mm, where L up ϭ Ldown ϭ 40 mm of the umbilical arteries, as well as the geometry of the Hyrtl anastomosis (D anast ϭ 4 mm, Lanast ϭ 8 mm), were chosen from averaged morphometric data (17)(18)(19)25). The downstream resistance of the arterial vasculature in the placental territories, which are supplied by each umbilical artery, is represented by a cylindrical porous media of length L porous ϭ 20 mm (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Hyrtl's anastomosis between the two umbilical arteries of single pregnancies has been described in pathological reports 6 , with the assumption that they influence the blood pressure in the placental bed and between the umbilical arteries 7 . We speculate that a fenestration occurred between the two umbilical vein walls because of their proximity.…”
Section: Letters To the Editormentioning
confidence: 99%
“…Functionally, Predanic et al (7) observed a small difference in resistance to blood flow between the two umbilical arteries, which diminished during late pregnancy indicating a functional maturation or adaptation of the anastomosis. In a few cases with perfectly symmetric umbilical artery supply areas, lack of anastomosis has been observed suggesting regression of even the last connection when shunting is not needed (1). The main function of Hyrtl's anastomosis is probably to equalize the flow and pressure in the two arterial placental vascular territories (10).…”
Section: Discussionmentioning
confidence: 99%
“…After thawing, the arterial tree of each placenta was filled with barium X-ray contrast medium and angiograms achieved in two perpendicular projections as described in earlier work (1,13). The anastomosis was measured and characterized in the angiograms according to our previous study in placentas from full-term AGA infants with normal umbilical artery blood flow (1).…”
Section: <0001mentioning
confidence: 99%
See 1 more Smart Citation